Early development of castor bean (Ricinus communis L.) phenology in different organic substrates (Research, Society and Development, 2021)
Germination is the process of growing a plant from the seed, which is in a latency state until good environmental conditions are found to germinate. This work aimed to monitor the initial development of castor bean (Ricinus communis L.) in pots with different organic substrates, evaluating the phenology of the plants. The experiment was carried out at the State University of Alagoas Campus I from January to December 2020, the experimental design was completely feetsrandomized with 4 treatments and 5 replications, soil with organomineral fertilizer (t1), soil with goat manure (t2), soil with manure beef and soil with carbonized rice husk (t4). The seeds used were collected in Girau do Ponciano - AL. The phenological follow-up data were registered in Excel spreadsheets, then the variables were submitted to analysis of variance, and for comparison of means the Tukey test (P < 0.05) was used by the SISVAR ® software. With the results obtained, it was found that there was no significant difference between the treatments used, regarding the development of plant phenology.